Polysilazane-based coatings: corrosion protection and anti-graffiti properties†. (3rd April 2019) - Rossi, S.; Deflorian, F.; Fedel, M.
ABSTRACT: Polyorganosilazanes (PSZs) are innovative materials which can be used to develop thin coatings of potential interest where corrosion protection, anti-graffiti and ease to clean properties are requested. In this work, the properties of polysilazane coatings deposited on AA1050 have been studied. A trialkoxysilylane substituted polymethyl-(hydro)/polymethylsilazane was employed to obtain 400–500 nm thick transparent coatings. The effect of four different curing temperatures (80–230°C) and four different curing times (30–180 min) on the final properties of the coatings has been evaluated. Electrochemical impedance spectroscopy measurements have been carried out in order to assess the corrosion protection properties of the deposited films. The temperature has been proved to have a greater influence on corrosion protection performance compared to the curing time. Contact angle measurements and marking/cleaning tests have been carried out to highlight the anti-graffiti properties.